2022
DOI: 10.4103/gmit.gmit_111_20
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Nondescent Vaginal Hysterectomy, Laparoscopy-Assisted Vaginal Hysterectomy, and Total Laparoscopic Hysterectomy for Benign Uterine Diseases at a Rural Tertiary Care Center

Abstract: Objectives: The aim of this study was to compare operative data and postoperative complications among nondescent vaginal hysterectomy (NDVH), laparoscopy-assisted vaginal hysterectomy (LAVH), and total laparoscopic hysterectomy (TLH) at a rural tertiary care center. Materials and Methods: This is a prospective analytical study, of 145 hysterectomies for benign conditions with or without salpingo-oophorectomy in women from 30 to 60 years, over 3 years from January 2016 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The mean weight of the uterus was 82.7 ± 45.1 grams. The study found no substantial changes in the weight of the uterus between women of different age groups or parity (9). Another study conducted by Octaviana et al examined hormonal levels in 100 women with irregular menstrual cycles.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The mean weight of the uterus was 82.7 ± 45.1 grams. The study found no substantial changes in the weight of the uterus between women of different age groups or parity (9). Another study conducted by Octaviana et al examined hormonal levels in 100 women with irregular menstrual cycles.…”
Section: Discussionmentioning
confidence: 90%
“…One study that investigated the weight of the uterus in Pakistani women measured the weight of the uterus in 126 women who underwent hysterectomy for benign conditions (9). The mean weight of the uterus was 82.7 ± 45.1 grams.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical approach many at times form the determining factor for postoperative surgical morbidity in patients especially in cases of abnormal uterine bleeding which is considered a diagnosis of exclusion. [ 8 9 ] It accounts for most of the referrals to the gynecological outpatient department and in the majority of patients, no organic pathology is identified that which makes it difficult to convince patients to medical management and follow-up, thus preferring surgical management as their ultimate solution. [ 10 ] The studies done previously have demonstrated a dependence of surgical morbidity not only on the surgeon’s degree of experience with the respective laparoscopic operation but also on the amount of experience with endoscopic procedures of the entire treating center.…”
Section: Discussionmentioning
confidence: 99%
“…Total laparoscopic hysterectomy (TLH) significantly increases ureteral injury risk compared to open abdominal hysterectomy. [ 1 2 3 ] In difficult cases, ureter dissection is important for preventing ureteral injury. [ 4 ] Dissecting the ureter is not always needed; however, in complicated cases, it is difficult for residents.…”
Section: O Bjectivementioning
confidence: 99%